Cases of Anthrax in Humans and Animal in Bogor at the Beginning 2001 - Susan M Noor; Darminto .; S Hardjoutomo (Indonesian Center for Animal Research and Development, 2001)
Anthrax is a zoonotic disease caused by Bacillus anthracis. The incidence of anthrax in human and animal has been reported in Indonesia including the case of anthrax in ostrich in Purwakarta in 1999. Virtually all animals, to some degree are susceptible to anthrax but ruminants are considered to be the most susceptible. There are 11 provinces in Indonesia reported as endemic areas. Retrospective study of anthrax in Bogor reported that the disease has been spread in nine areas. The manifestation of human anthrax could be visceral, cutaneus, pulmonum, meningitis or combination but the cutaneus type is the most frequent (95%). In early 2001, there was an outbreak of anthrax affecting both human and animals in Bogor. A definitive diagnosis of anthrax has been made in 5 people in Hambalang village, Citeureup subdistrict of Bogor. The objective of this study is to describe the chronological event of the recent anthrax wabah in Bogor and to give a brief discussion of anthrax in human and animal. Key word: Antraks cases, human beings, animals, Bogor, 2001